2005
DOI: 10.1093/jac/dki264
|View full text |Cite
|
Sign up to set email alerts
|

Potent synergic effect between ibuprofen and azoles on Candida resulting from blockade of efflux pumps as determined by FUN-1 staining and flow cytometry

Abstract: Resistance related to overexpression of efflux pumps was common among clinical isolates and could be reverted by the assayed modulators, particularly ibuprofen. The mechanism of resistance in all tested C. krusei and in a few other strains seems, however, to be of a different nature. Ibuprofen is a promising compound in association with azoles, deserving future clinical trials. FUN-1 proved to be a good marker of efflux in Candida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 24 publications
1
61
0
1
Order By: Relevance
“…[20,22]. Also, Ibuprofen show fungistatic activity at low concentrations and fungicidal activity at high concentrations [23]. In this study we tested the antifungal activity of three NSAIDs on different Candida Spp.…”
Section: Introductionmentioning
confidence: 99%
“…[20,22]. Also, Ibuprofen show fungistatic activity at low concentrations and fungicidal activity at high concentrations [23]. In this study we tested the antifungal activity of three NSAIDs on different Candida Spp.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combination of CAS1 (4 g/ml) with AMB (0.25 g/ml), as well as that of CAS2 (8 g/ml) with VRC (4 g/ml) was used to inhibit the biofilm of A. fumigatus AF293. This combination was used as a model to observe the synergistic activity against Aspergillus biofilm by FUN-1 staining (8,15). With an Olympus FV-500 laser scanning confocal microscope, we observed that the amount of viable organisms in the A. fumigatus AF293 biofilm was significantly less when being treated with these drugs-CAS1 (4 g/ml) with AMB (0.25 g/ml) or CAS2 (8 g/ml) with VRC (4 g/ml) (see Fig.…”
mentioning
confidence: 99%
“…To reverse fungal FLC resistance, a putative chemosensitizer should be nontoxic in the absence of FLC but render a normally FLC-resistant strain more sensitive to FLC. Inhibitors of fungal ABC transporters include FK506 (30,42), enniatin (13), milbemycins (20), unnarmicins (48), isonitrile (56), disulfiram (44), ibuprofen (36), and quinazolinone derivatives (51). Such inhibitors, or chemosensitizers, may act indirectly on aspects of metabolism that affect efflux.…”
mentioning
confidence: 99%
“…FK506, for example, used in cancer chemotherapy as an immunosuppressant, may act both directly (since overexpression of Cdr1p significantly reduces susceptibility to FK506) (30,42) and indirectly (by effects on the calcineurin pathway) (2,12,46,47,49) to reverse resistance to FLC in fungi. Ibuprofen is a potent anti-inflammatory and analgesic drug, which at low concentrations inhibits azole efflux from C. albicans, and has been proposed for combination treatment of fungal infections with FLC (36).…”
mentioning
confidence: 99%